Identifying of emotional quotient junior high school students in mathematics - Syaiful Syaiful; Kamid Kamid; Nizlel Huda (Institute of Advanced Engineering and Science, 2021)
This study aimed to determine the emotional intelligence of junior high school students, especially in managing emotions, recognizing emotions, and motivating themselves. This was quantitative study with survey design. There were 102 respondents participated in this research that were obtained based on purposive technique. The instruments used in this study were questionnaires and semi-structured interviews and data analysis using descriptive statistics, including mean, min, max, categorization, and percentage. From the results of the investigation that has been done, it is found that there is emotional intelligence of students in mathematics which is shown by the aspect of recognizing emotions which has a suitable category of 61.8% (63 of 102) students, the issue of managing emotions has an appropriate category of 53.9% (56 out of 102) students. The self-motivation aspect has a suitable category of 60.8% (62 out of 102) students. Students need to be allowed to develop direct experiences and thoughts on learning activities.